Antibiotic prescribing trends among US dermatologists in Medicare from 2013 to 2016. (2nd January 2021) - Kakpovbia, Efe; Feng, Hao; Feng, Paula W.; Cohen, Jeffrey M.
Abstract: Objectives: Antibiotics are commonly used in dermatology for infectious and inflammatory diseases, and dermatologists prescribe the most antibiotics per physician of any specialist in the United States (US). While oral antibiotics are effective for many conditions, adverse effects and increase in resistance are important public health issues. The purpose of this study is to examine trends in oral antibiotic prescription by US dermatologists using Medicare claims. Materials and Methods: Retrospective review using publicly available Medicare Part D prescriber public use files from 2013 to 2016. Results: The number of dermatologists within the Medicare system increased from 10, 210 to 10, 749. The proportion of prescriptions by dermatologists that were oral antibiotics increased from 10.0% to 10.7% ( p  = .023). The use of oral antibiotics increased 10.1% (2.9 claims per 1, 000 beneficiaries) from 28.7 to 31.6 claims per 1, 000 beneficiaries. There were more oral antibiotic prescriptions in the South than in other regions. Doxycycline was the most commonly prescribed antibiotic each year in all regions. Conclusions: Between 2013 and 2016, the number of oral antibiotics prescribed by dermatologists has increased among Medicare patients. Dermatologists must continue to reevaluate antibiotic prescription practices, particularly among the elderly population, in order to provide optimal care to patients.